IMPROVING CUSTOMERâS EXPERIENCE TO GAIN COMPETITIVE ADVANTAGE: INNOVATION OF 5G ON CLOUD GAMING - Subhodeep Ganguly, Muhammad
The gaming industry is a major part of popular culture and has a substantial impact on the economical aspect in business with unlimited potential for growth. It is a USD$139 billion a year business and like any tech-related industries it is continually evolving as the years go by. This paper specifically examines how 5G technology may influence customer experience in cloud-gaming. Cloud-gaming in general has been around for a while but only now that companies are taking serious measures to dive deep into the potential capabilities of what the technology can offer. Thus this research covers how 5G’s capabilities can play an important role in shaping customer experience to create a competitive advantage in the cloud-gaming sphere. The fundamental theory used for this study is resource-based view and dynamic capabilities where the analysis will revolve around how the industry’s firms rely on renewing their capabilities while also implementing old capabilities with new technology to create a competitive advantage in the market. Since there are many topics and research regarding cloud-gaming, latency issues and 5G potential, the expectation is that 5G can greatly improve the streaming quality of cloud-based games thus improving customer experience and reaffirms a company’s competitive advantage. The discussion presented from this study mainly boils down to how a brand new network technology such as 5G, can affect customer experience to gain a competitive advantage in the cloud sector of the gaming industry. The research analyzed the developments of 5G and how it can affect customer experience which can influence customer engagement on the product; this can help determine how will companies in the future make use of 5G technology to stay competitive, while also giving an informed speculation for the readers of the potential changes that will occur in this industry. The discussion in the study provided shows the development of networks in the future, by using 5G to improve customer experience through 4 aspects; these are, latency, lag compensation, matchmaking and in-game contents. 5G will drop or even completely abolish latency while lag compensation techniques can be greatly improved, in-game contents will likely to grow as there are less threshold for developers to create content and matchmaking will be much quicker, leading to more engagement. Without 5G, improvements on these four aspects in cloud-gaming will be very small and will not provide the major push the gaming industry needs for consumers to change their behavior of playing physical video game products. The research question proposed for this study is how does the integration of 5G to cloud- gaming infrastructure increase customer experience to gain a competitive advantage?